Flexural-slip folding in buckling phases of orogenic belts: Insight into the tectonic evolution of fault splays in the East Iran orogen - Rashidi, Ahmad; Shafieibafti, Shahram; Nemati, Majid; Ezati, Maryam; Gholami, Ebrahim; Mousavi, Seyed Morteza; Derakhshani, Reza (Frontiers in Earth Science, 2023)
The East Iran orogen has undergone multiple buckling phases, leading to the formation of various scale refolding features known as strike-slip faults splay. The geometric and kinematic characteristics of these splay features are a result of the folding mechanisms. This study investigates the structural characteristics and tectonic evolution model of the Khousf splay in the northern terminus of the Nehbandan right-lateral strike-slip fault system. The results of the field visits and geometrical properties from the map view indicate that the splay includes a multi-plunging anticline and syncline (referred to as the Khousf anticline and Khousf syncline), with flexural slip being an essential mechanism for its formation. Structural evidence suggests that flexural slip occurred on discrete movement horizons among the rock units, resulting in the formation of structures such as parasitic folds, active folds, and strike-slip duplexes. The parasitic folds with M, W, Z, and S shapes in the cores and limbs of the Khousf anticline and syncline were analyzed, and complex slicken-line patterns on the faults parallel to the beds at the limbs were observed. The analysis results emphasize the strain partitioning and inclined left- and right-lateral transpressional zones. The shortening estimated through the NE-SW, N-S, and NW-SE profiles of the common limbs of the anticline and syncline in the Shekarab inclined transpressional zone is approximately 33%, 65%, and 68%, respectively. In the Arc area (the core of the anticline), the estimated shortening through the NE-SW and N-S profiles is 14% to 10%. The structural analysis of the folds in this area indicates that the folds have broad, close, semi-elliptical, and parabolic shapes. The study concludes that the secondary folds with NW-SE axis directions have been superimposed on the first-generation folds with E-W axis directions in the Khousf refolded splay.